2018
DOI: 10.1080/21650349.2018.1463176
|View full text |Cite
|
Sign up to set email alerts
|

Design creativity: refined method for novelty assessment

Abstract: Novelty is an important characteristic of a creative idea, forming a core component of creativity. Measurement of novelty is therefore essential to assess creativity. We found deficiencies in a frequently cited method of novelty assessment found in the literature. We refine this method by proposing four modifications, supported by drawing on examples of products and ideas. The refined method and the original method are evaluated by benchmarking them against the collective, intuitive assessment of product novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 20 publications
0
30
1
1
Order By: Relevance
“…a mere structural detail). This can be in contrast with literature asserting that the abstraction level should play an important role in novelty assessments: the higher is the abstraction level in which the difference is observed, the higher is the novelty (Jagtap, 2016;Sarkar and Chakrabarti, 2011). Moreover, in presence of incomplete solutions, e.g.…”
Section: Jansson and Smithcontrasting
confidence: 69%
“…a mere structural detail). This can be in contrast with literature asserting that the abstraction level should play an important role in novelty assessments: the higher is the abstraction level in which the difference is observed, the higher is the novelty (Jagtap, 2016;Sarkar and Chakrabarti, 2011). Moreover, in presence of incomplete solutions, e.g.…”
Section: Jansson and Smithcontrasting
confidence: 69%
“…Novelty is a core component of creativity, and novelty seeking is often a prerequisite to creativity assessment ( Jagtap, 2019 ). As early as in the 1950s, Morgan (1953) reviewed definitions of creativity and concluded that creativity is centered on the concept of novelty.…”
Section: Introductionmentioning
confidence: 99%
“…Innovation requires that a product should be both novel and successful in its objectives. When assessing the output of GPD systems, it is crucial that researchers follow the most recent practices for assessing and validating novelty [77][78][79]. This is an important shortcoming of all the systems reviewed here.…”
Section: Achievement Of Goals and Limitationsmentioning
confidence: 99%